The Role of Bureaucratic Reform in Improving the Performance of the Gayungan Surabaya Police Sector - Trie Sis Biantoro; Anang Kistyanto; Sanaji Sanaji (International Journal Business, Management and Innovation Review, 2024)
Effective and responsive bureaucracy is an important factor in achieving efficiency and professionalism within police institutions. This research identifies the problems faced by the Gayungan Surabaya Sector Police regarding bureaucratic reform to evaluate the impact of bureaucratic reform on institutional performance. This study uses a qualitative approach in its research, involving the use of data collection methods such as participant observation, in-depth interviews, documentation, and focus group discussions. The informants in this research are members of the Gayungan Surabaya Sector Police who are actively involved in HR management. Data were analyzed using qualitative data analysis methods. This research is expected to be able to identify problems that arise in the bureaucratic reform process and evaluate the impact of the reform. In addition, this research aims to provide policy recommendations that can improve the performance of police institutions in terms of efficiency, responsiveness and professionalism. The contribution of this research is to provide a deeper understanding of the importance of bureaucratic reform in improving the performance of police institutions, as well as contributing to the development of human resource management theories, such as change management and Strategic Human Resource Management (SHRM), which emphasizes the integration of HR policy with strategy organization.